2022
DOI: 10.1002/we.2796
|View full text |Cite
|
Sign up to set email alerts
|

Helical vortex theory and blade element analysis of multi‐bladed windmills

Abstract: Multi-bladed windmills usually pump water for agriculture and domestic consumption, often in remote locations. Although they have been around for over 150 years, their aerodynamic performance is still poorly understood. This paper describes the use of helical vortex theory (HVT) and blade element momentum (BEM) analysis to predict windmill thrust, torque, and extracted power. We emphasize the unusual features of windmills: low Reynolds numbers and tip speed ratios and high solidity, all related to the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Since modern turbines have λ opt ∼ 7 − 9, the highthrust region normally spans high values of λ: as a rule of thumb λ R ≈ 2λ opt . This approximate relation holds for multiblade windmills where λ opt ∼ 1, as shown in Figure 5 of John et al (2023), and the experiments of Krogstad and Adaramola (2012) and Krogstad and Eriksen (2013) that we consider below, for which λ opt ∼ 6. Furthermore, it is normal for C T to increase monotonically in this region when λ opt is large.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Since modern turbines have λ opt ∼ 7 − 9, the highthrust region normally spans high values of λ: as a rule of thumb λ R ≈ 2λ opt . This approximate relation holds for multiblade windmills where λ opt ∼ 1, as shown in Figure 5 of John et al (2023), and the experiments of Krogstad and Adaramola (2012) and Krogstad and Eriksen (2013) that we consider below, for which λ opt ∼ 6. Furthermore, it is normal for C T to increase monotonically in this region when λ opt is large.…”
Section: Introductionmentioning
confidence: 64%
“…Our revisions to BEMT apply at all values of λ including zero, but we concentrate on the high-thrust region, where BEMT is most challenged. It is further noted that John et al (2023) found conventional BEMT accurately predicted λ R for a model of a lowspeed, multi-bladed water pumping windmill where λ R ≈ 2 and the runaway C TR increased from 0.1 to 0.5 as N increased from 3 to 24. The implication is that the present revisions are not critical at low λ.…”
Section: Introductionmentioning
confidence: 82%
“…As the rotor extracts kinetic energy from the flow, the stream velocity heavily decreases along the rotor center line due to the blockage effect imposed by the rotor on the diffuser-confined flow. According to [30], the blockage effect can significantly impact the rotor performance as it alters the flow around the blades, and it is a function of the number of blades [31]. The calculated turbulent kinetic energy (TKE) is shown in Figure 12 on a logarithmic scale.…”
Section: Performance Of the Diffuser-augmented Hydro Turbinementioning
confidence: 99%
“…Although there are several publications on the design and performance analysis of small horizontal-axis wind turbines [16,17], further investigation is required to examine the effects of swept blades on the starting and operational performance of small horizontal-axis wind turbines. The authors are unaware of any study on this regard.…”
Section: Introductionmentioning
confidence: 99%